Thermal Performance of Roofing Systems In Relation To the Mean Radiant Temperature in Malaysian Residential Buildings - Lau, Allen Khin Kiet (2008)
Malaysian housing industry is facing a huge challenge to provide environmentally sustainable housing developments. The main issue concentrates on thermal performance of building envelopes to improve thermal comfort and energy savings. The major problem of Malaysian domestic housing development is the over heating of roof space caused by inappropriate roofing systems and materials as the roof is the major source of heat gain. The excessive heat gained from the sun will be radiated from the roof space to the occupants through radiation. Previous studies were done on the evaluation of thermal performance of roofing systems for residential buildings in Malaysia, based on air temperature measurement. However, there is no study focusing on the effect of roofing systems on Mean Radiant Temperature, which will have a direct impact on the thermal exchange between the roof and the occupants. Mean Radiant Temperature of a space is the measure of the combined effects of temperatures of surfaces within that space such as roof, walls and floor. Therefore, the main objective of this study is to investigate the effect of roofing systems and materials on Mean Radiant Temperature for recommendations of roofing systems and materials for optimum thermal performance under Malaysian climate. This research involved an observation survey on the common roofing systems and materials for recent domestic housing developments in Malaysia. This was followed by simulations of Mean Radiant Temperature by using the simulation software, Heat Transfer in Buildings HTB2 to evaluate thermal performance of various roofing systems and materials based on the observation survey. Field measurements on Mean Radiant Temperature at first floor level of a double storey terrace house in Kuala Lumpur were then carried out by using INNOVA thermal comfort measurement tools. The measured Mean Radiant Temperature was compared with the simulated Mean Radiant Temperature for validation of the software. The results revealed that among common roofing systems and materials in recent Malaysian domestic housing industry, clay tile with double sided aluminium foil and plasterboard ceiling is able to produce the optimum thermal performance in relation to Mean Radiant Temperature. This is followed by concrete tile roofing system with double sided aluminium foil and plasterboard ceiling, and lastly metal deck roofing system with double sided aluminium foil, rockwool as insulation materials and plasterboard ceiling. From the simulation results, the most effective location for aluminium foil is below the roof tiles compared to on top of horizontal ceiling. However, it is recommended that with additional combination of double sided aluminium foil on top of plasterboard or rockwool as hybrid ceiling, it will significantly reduce indoor Mean Radiant Temperature. This will reduce the heat exchange between the roof space and the occupants through radiation, and therefore optimising thermal performance of roofing systems under Malaysian climate. In conclusion, this study demonstrates the importance of choosing appropriate roofing systems and materials for better thermal comfort through the understanding on the effect of roofing systems on Mean Radiant Temperature. The recommended roofing systems and configurations will become useful guidelines for developers, architects, and house owners to improve thermal comfort of residential buildings in Malaysia. Therefore, this study will contribute in promoting energy and cost savings in Malaysian housing industry, as well as the whole country’s development.